Profil Klinis dan Kesintasan Pasien Karsinoma Sel Hati di Rumah Sakit Rujukan Tersier Indonesia Tahun 2015-2021 - Hasan, Irsan; Gani, Rino Alvani; Sulaiman, Andri Sanityoso; Kurniawan, Juferdy; Lesmana, Cosmas Rinaldi A.; Jasirwan, Chyntia Olivia M; Nababan, Saut Horas H.; Kalista, Kemal Fariz; Aprilicia, Gita; Teressa, Maria (UI Scholars Hub, 2023)
Introduction. Hepatocellular carcinoma (HCC) is the most common primary liver cancer in the world and Indonesia. This study aimed to describe the clinical presentation and survival rate of HCC patients in Dr. Cipto Mangunkusumo Hospital (RSCM) as the Indonesian tertiary referral hospital in year 2015-2021 Methods. Cohort study was performed in year 2015-2021. Clinical presentations at the time of diagnosis were recorded from electronical health record. All HCC patients were followed up until death. One-year survival based on staging was assessed using log rank test and presented with Kaplan Meier curve. Results. A total of 799 HCC patients were included. Majority of HCC patients were male, 619 patients (77.5%), and aged 55 (SD 11.9) years. Hepatitis B was the major etiology, found in 500 patients (62.6%). Median of alfa feto-protein (AFP) was 1,109 (0.8-3,462,499) ng/ml. At the time of diagnosis, Barcelona Clinic Liver Cancer (BCLC) stage C (37.7%) was the most commonly found. Portal vein thrombosis was found in 205 patients (25.7%). There were 271 (33.9%) HCC patients received curative and palliative treatment, and others had supportive care. One year survival rate of HCC was 61.2%. One year survival rate of HCC based on staging for BCLC A, BCLC B, BCLC C, and BCLC D were 91.1%, 68.6%, 47.6%, and 13.3%, respectively (log-rank test: p<0.001). Conclusion. The majority of patients diagnosed with HCC were at an advanced stage so that the one-year survival is poor.